Productivity dynamics and the productivity trap: problems and solutions in Latvia - Jekabsone, Sandra; Skribane, Irina (University of Latvia, 2019)
By analysing changes in productivity and labour costs in Latvia from 2013 till 2017, we can see that growth of labour costs exceeds the growth of productivity by more than 2 times in both, tradable sector and total economy. Slow growth in productivity compared with the labour and other production expenses lead to an increase in the price of final goods and services, which negatively corresponds with producers’ competitiveness in both internal and external market. Furthermore, this leads to a drop-in consumption of domestic production and inefficient production facility usage, resulting in declining economic growth rates. The rapid growth in labour costs is mainly associated with the tight situation in the labour market. Even though the unemployment rate is still quite high, especially in the region of Latgale, the absence of working hands is perceptible more and more around Latvia, which also maintains the pressure on the salaries. The upward trend for salaries is also influenced by the convergence process, which is inescapable in EU opened labour markets. Comparatively, high labour emigration reflects Latvia’s weak competitiveness in those markets, especially due to the low wage, which in turn is related to the low productivity of internal producers. Therefore, increasing the productivity level and slowing down the gap of productivity with highly developed countries is the most important precondition for Latvia’s competitiveness to strengthen and economy to grow. The goal of the research is to appreciate the dynamics of labour productivity and the level of productivity between Latvia and EU average, as well as, to find the main factors which influence the productivity convergence rates to drop, making productivity trap. The research tasks, to determine possible solutions for labour productivity increases, are to detect the factors which have influenced the labour productivity in last 10 years in Latvia, to compare the productivity in Latvia with EU, as well as, to detect the factors which influenced the productivity convergence rates to decrease. In the analysis, there are used different high quality and quantity research methods, for example, analysis of scientific literature, calculation of average and relative sizes, grouping, comparison, decomposition etc. The results of research conclude, that in the last years productivity growth rates in Latvia before the crisis (2000-2007) were one of the sharpest in EU, which contributed with convergence process, decreasing gap with EU average by 2 pp. annually. However, in after crisis period (from 2011) growth rates of productivity have significantly dropped and the convergence process became more moderate - only 0.8 percent points at average a year, which shows that Latvia is close to or already is into productivity trap. To avoid the trap, it is important to detect separate industry problems (the stud of barriers at individual company and sector level) and to promote the structural changes in the national economy (moving towards high technology industries).
Keywords: productivity trap; labour cost; economic growth; structural changes; Research Subject Categories::SOCIAL SCIENCES::Business and economics